Les organisations professionnelles agricoles et la gestion des ressources naturelles en Amazonie brésilienne orientale : Innovations et apprentissages - Laurence Granchamp Florentino; Aquiles Simões (VertigO)
In the eastern Brazilian Amazon, the family farming and rural organisations – we called ‘OPAR’ (associations, unions, federations of small farmers’ unions, NGOs arisen from the rural movement) - have acceded to an operational or intermediation role, which place them in a strategic position for the implementation of natural resources management projects. So, they operate, locally, several programs for the protection of the rain forest promoted by the NGOs or international organisations, or corresponding to federal public policies. We question here the conditions of emergence of this collective actor in the field of sustainable development and the work of political construction of a convergence between the problems of the family farming and those of the environment. More widely, the interaction of the various agents of the development requires learning that we formalized in a frame adapted to the regional context: the "cloth (canvas) of social learning ".